2007
DOI: 10.1116/1.2750345
|View full text |Cite
|
Sign up to set email alerts
|

Initial stages of GaP heteroepitaxy on nanoscopically roughened (001)Si

Abstract: GaP heteroepitaxy on Si(001): Correlation of Si-surface structure, GaP growth conditions, and Si-III/V interface structure J. Appl. Phys. 111, 083534 (2012); 10.1063/1.4706573Thickness inhomogeneities and growth mechanisms of GaP heteroepitaxy by organometallic chemical vapor deposition J.The authors report real-time spectroscopic-polarimetric determinations of the initial phase of GaP heteroepitaxy by organometallic chemical vapor deposition on nanoscopically roughened ͑NR͒ ͑001͒Si substrates, where polarimet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Recently, we reported successful growth of epitaxial GaP layers on Si substrate using MOVPE [10]. Liu et al [14] reported on the initial growth mechanism using in-situ measurements. Here, we report a two-step growth process of GaP epilayer on Si substrate using MOVPE, which includes the growth of a low-temperature GaP nucleating layer and a high-temperature GaP epilayer.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, we reported successful growth of epitaxial GaP layers on Si substrate using MOVPE [10]. Liu et al [14] reported on the initial growth mechanism using in-situ measurements. Here, we report a two-step growth process of GaP epilayer on Si substrate using MOVPE, which includes the growth of a low-temperature GaP nucleating layer and a high-temperature GaP epilayer.…”
Section: Introductionmentioning
confidence: 97%
“…To explore these issues, a number of groups have investigated the growth of GaP layers on Si substrates using metal organic vapor-phase epitaxy (MOVPE) [1,[8][9][10][11][12], molecular beam epitaxy (MBE) [5] and chemical beam epitaxy [13]. The MOVPE growth of high crystalline quality GaP on Si is still a challenging task [10,14]. Recently, we reported successful growth of epitaxial GaP layers on Si substrate using MOVPE [10].…”
Section: Introductionmentioning
confidence: 99%
“…The initial metallic gallium concentration is reduced, but not eliminated. For comparison, the initial growth rate of GaP on (001)GaAs under these conditions is one order of magnitude smaller and no metallic Ga is present [8]. The significant differences in chemical reactivities among nr(001)Si, (001)GaAs and (001)GaP also show that growth under present conditions is kinetically limited.…”
Section: Methodsmentioning
confidence: 89%
“…Here, we investigate growth of GaP on nanoscopically roughened (nr-) (001)Si in an organometallic chemical vapor deposition (OMCVD) reactor, providing additional results and a possible alternative interpretation that complement our earlier publication on this topic [8]. With a lattice mismatch of only 0.37%, GaP on Si is a good test case.…”
mentioning
confidence: 85%
“…Low temperature nucleation is beneficial to reduce interface roughening, which was observed, e.g., by in situ ellipsometry for nucleation at 600 °C. Detailed in situ studies—combining RAS, p‐polarized reflectance spectroscopy, and laser light scattering during pulsed GaP nucleation by chemical beam epitaxy as well as polarometry in MOVPE—revealed that TBP reacts immediately upon adsorption on the growth surface, and that the amount of Ga must be precisely balanced to minimize surface roughening, 3D nucleation, and Ga droplet formation . 3D nucleation is also reduced when applying high V:III ratios .…”
Section: Internal Interfaces Of Epitaxial Heterostructuresmentioning
confidence: 99%